Prospects for the development of the library network in Dagestan in 1950s: a gender approach - M. K. Nagieva (Вестник Майкопского государственного технологического университета)
In the modern society government authorities pay quite a lot of attention to the development of the socio-cultural sphere in the country. Despite the fact that at the end of the 20th - beginning of the 21st century, libraries began to take on the functions of abolished cultural centers due to a significant reduction in the network of socio-cultural institutions. The functions of information centers have been added to the traditional functions of an educational nature, preservation and enhancement of cultural heritage, providing access to national and global information networks and databases. Today, modern library science presents new analytical capabilities for the study and analysis of library communications. One of these is a gender perspective, which looks at the norms and cultural symbols that men and women bring to the library profession.   The purpose of the research is to study this aspect in the socio-cultural sphere at the regional level, which allows us to trace the uniqueness of general processes within individual national republics.   To achieve this goal, the task has been formulated to reflect the history of the development of the library network in 1950s in the region using a gender approach. In the research methods of comparative historical analysis were used, as well as the principles of objectivism and historicism, which provided the opportunity to analyze various episodes and phenomena from a historical point of view. When studying the questions posed, the author has come to the conclusion that Russian historiography today has almost no research devoted to the study of the development of librarianship through the prism of gender stereotypes. This study is an attempt to highlight the development of librarianship, with an emphasis on women's experiences in this profession.